2010
DOI: 10.1021/jz101297r
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Oxygen Reduction Reaction Activity via Pd−Au Alloy Sublayer Mediation of Pt Monolayer Electrocatalysts

Abstract: New Pt monolayer electrocatalysts were prepared using galvanic displacement of a copper monolayer deposited at underpotentials on a Pd core. By performing underpotential deposition twice, two monolayers were deposited, forming a core-shell structure with double shells. The double shells consist of an outermost shell of Pt monolayer and a sublayer shell of Pd-Au alloy. It was found that by adjusting the compositions of the alloy sublayer, it is possible to mediate the oxygen reduction reaction (ORR) activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 39 publications
(70 reference statements)
8
124
0
Order By: Relevance
“…Higher electrocatalytic properties from Pt-alloys as well other noble metals-alloys over Pt, have been related with different phenomena broadly classified as: i) structural, ii) electronic and iii) surface sensitive factors [8,9]. For example, different studies have revealed that modifying the M 1 eM 2 distance through lattice contraction or expansion due to alloying effect, may decrease the OH adsorption energy on Pt-alloy increasing ORR activity [10,11]. However, it is necessary to mention that both geometric and electronic effects are intimately entrenched, thus, separating these effects and assessing their relative importance in the electrocatalytic activity and reaction mechanism, is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Higher electrocatalytic properties from Pt-alloys as well other noble metals-alloys over Pt, have been related with different phenomena broadly classified as: i) structural, ii) electronic and iii) surface sensitive factors [8,9]. For example, different studies have revealed that modifying the M 1 eM 2 distance through lattice contraction or expansion due to alloying effect, may decrease the OH adsorption energy on Pt-alloy increasing ORR activity [10,11]. However, it is necessary to mention that both geometric and electronic effects are intimately entrenched, thus, separating these effects and assessing their relative importance in the electrocatalytic activity and reaction mechanism, is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improved, lowcost ORR electrocatalysts with high activity, and increased potential for commercialization, can be obtained based on this approach. [38]. The above example evidently demonstrated the meditation effect of the interlayer for the interaction between Pt monolayer and the metal core.…”
Section: Addition Of An Interlayer Between the Ptmentioning
confidence: 72%
“…In another example, Tao et al [312] modified a Cu-UPD process by carefully preparing a UPD solution containing Cu, CuSO 4 and AA to allow the process to be free of potential control, resulting in 1~2 nm Pt nanoclusters being deposited onto Pd nanorods. Adzic et al [289] also performed the Cu-UPD twice to deposit double shells consisting of an outmost monolayer shell of Pt and a monolayer subshell of PdAu onto a Pd core.…”
Section: Principles and Development Of Electrodepositionmentioning
confidence: 99%